Proposed Model to Implement High-Level Information Security in Internet of Things - Castilho, Sergio Duque; Godoy, Eduardo P. [UNESP]; Castilho, Tayane W. L. [UNESP]; Salmen, Fadir; IEEE (Ieee, 2017)
Internet of Things (IoT) connect different types of devices to control different things or simply read data from then, such as room temperature, location, pressure and others, in a variety of application domains using the World Wide Web. This is a challenge for technology and Information Security (IS). Therefore, this paper surveys advances in IoT-based with an eye towards security, where discusses the technologies used in devices, the risks to which these devices are exposed to stay directly connect to a global network, the TCP/IP Network Layers Model that is used in this connection. The main objective of this paper is to propose an implementation models of security based on ISO 7498-2 for residential and industrial use in IoT. Mitigate risk is a major job for users of this technology because all Internet-connected device runs the risk of having their availability or integrity data transmitted corrupted.
Keywords: Internet of Things; IoT; Information security; Protocols